Effect of Metarhizium anisopliae fungus on off-host Rhipicephalus (Boophilus) microplus from tick-infested pasture under cattle grazing in Brazil - Garcia, Marcos Valerio [UNESP]; Monteiro, Antonio Carlos [UNESP]; Juan Szabo, Matias Pablo [UNESP]; Mochi, Dinalva Alves [UNESP]; Simi, Lucas Detogni [UNESP]; Carvalho, William Mendes [UNESP]; Tsuruta, Suzana Akemi [UNESP]; Barbosa, Jose Carlos [UNESP] (Elsevier B.V., 2011)
This work aimed to assess the effect of the fungus Metarhizium anisopliae on off-host Rhipicephalus (Boophilus) microplus from tick-infested Brachiaria decumbens pasture undergoing cattle grazing. For this purpose a naturally tick-infested Brachiaria decumbens pasture of 60 m x 100 m with twelve grazing Holstein Friesian-Nelore (Bos indicus) cross breed bovines was sprayed 12 times, 21 days apart with an aqueous conidial suspension of the E9 isolate of M. anisopliae fungus. Control pasture was treated with conidial suspension vehicle only. Efficacy of treatment was evaluated by tick larvae counts on the pasture and that of engorged female ticks on grazing cattle. Fungus persistence on grass stems as well as soil pasture was assessed after each spray. Efficacy of fungus against ticks was also measured by an in vitro immersion test. Whereas in vitro test showed a clear pathogenic effect of the fungus on ticks, no pathogenic effect over R. (B.) microplus ticks was detected in the field trial by spraying pasture with fungal suspension. Fungus from the suspension could be recovered from both the grass stem as well as the soil of sprayed pasture, even though the numbers obtained varied distinctly and could only be recovered shortly after spray. Pasture environments with exposure to sun and rain, seem to be very detrimental to the fungus, thus suspensions which provide fungus with protection or more resistant isolates to these should be looked for. In order to achieve high fungal efficacy against tick under field conditions, accurate laboratory assays, optimization of application strategy and knowledge of interactions between fungal strains and environmental factors are warranted. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Biological control; Entomopathogenic fungus; Cattle tick; Brachiaria decumbens